Becoming an International School Educator : stories, Tips, and Insight from Teachers and Leaders - Specker Watts, Dana, ....-; Richardson, Jason W., ....- (New York : Routledge, 2022)
This resource elucidates and helps teachers navigate the international school recruitment world. Designed for current or aspiring international school educators, this practical resource explores current issues that are relevant to the unique needs of teachers when they transition to the international school sector. Full of experience-based tips, insights, and stories from principals, curriculum coordinators, directors, school counselors, department heads, support specialists, advisors, and classroom teachers, this book explores the topics of wanderlust, English language teaching, identity and belonging, curricular standards, inclusion, diversity, and equity. Whether you are a student or novice teacher plotting career options, a new international school hire, or an experienced educator looking for a rewarding change, this valuable resource will help you prepare as you embark on what is often considered "the best kept secret" in education.
Keywords: International school educator; International school recruitment world